Widely tunable, high optical signal-to-noise ratio erbium-doped photonic crystal fiber laser suitable for acetylene sensing. (January 2019) - Zhang, Min; Zhong, Xuesen; Zheng, Wanjun; Ruan, Shuangchen; Du, Bin; Yan, Peiguang; Liang, Huawei; Liu, Chengxiang; Li, Ling; Su, Hong
Highlights: Using an erbium-doped photonic crystal fiber was used as a gain medium. The stable laser output has wavelength step lengths below 0.02 nm. The laser can align the acetylene absorption peak with high precision. The laser had a maximum fluctuation in wavelength less than 6 pm (2h). The peak power standard deviation was ∼0.03 dB during the 2 h experimental time. Abstract: Narrow line-width fiber lasers are useful in gas-sensing, but systems that are both tunable and stable are rare. Here, we describe a single-wavelength ring cavity erbium-doped photonic crystal fiber laser (ED-PCFL) that can align the acetylene (C2 H2 ) gas absorption peak with high precision and a maximum deviation less than 0.012 nm. Rather than using a combination of erbium-doped fiber and a strong nonlinear fiber, ED-PCF was used as a gain medium to achieve a stable single-wavelength output based on the non-linear polarization rotation effect (NPR). This was selected because ED-PCF has a strong nonlinear effect. We added the dual polarization controllers (PCs) to weaken the homogeneous broadening based on the traditional tunable filter (TF) filtering structure. The results show that these steps improve the tunability of the laser wavelength and enhance the stability of the light source. The final laser had a side-mode suppression ratio as high as 60 dB over 45 nm with a maximum fluctuation in wavelength less than 6 pm. The peak power standard deviation was ∼0.03 dB during the 2 h experimental time. The peak power response of ED-PCFL was studied as a function of C2 H2 concentrations, and the calculated R-squared value was 0.993. This means that the ED-PCFL is suitable for C2 H2 sensing.